Novel utilization of 3D technology and the hybrid operating theatre: Peri‐operative assessment of posterior sterno‐clavicular dislocation using cone beam CT. Issue 2 (4th June 2013) - Crowhurst, James A.; Campbell, Douglas; Whitby, Mark; Pathmanathan, Pavthrun
Abstract A patient with a medial and posterior dislocation of the right sterno‐clavicular (SC) joint and displacement of the trachea and brachiocephalic artery by the medial head of the clavicle underwent general anaesthetic in the operating theatre for an open reduction procedure. The surgeon initially attempted a closed reduction, but this required imaging to check SC alignment. The patient was transferred to an adjacent hybrid operating theatre for imaging. Cone beam computed tomography (CBCT) was performed, which successfully demonstrated a significant reduction in the dislocation of the SC joint. The trachea and brachiocephalic artery were no longer compressed or displaced. This case study demonstrates an alternative to the patient being transferred to the medical imaging department for multi‐slice CT. It also describes a novel use of the hybrid operating theatre and its CBCT capabilities.